Correlates of Knowledge Regarding Utility of Soil Testing and Soil Health Card - Patel, G.G.; Lakum, Y.C.; Mishra, Aakash; Bhatt, J.H. (Indian Journal of Extension Education, 2019)
It is always important to find out the factor responsible for positive or negative disposition associated with farmer toward the usefulness and application of any innovation as change in knowledge preceded acceptance and application of an innovation. The present investigation was undertaken in Petlad taluka of Anand district in middle Gujarat region. The random sampling of one hundred farmers from Petlad taluka was done based on number of respondent who had soil health cards. The results revealed that 52 per cent respondent belonged to high to very high category with respect to knowledge of soil testing. These farmers adopted the technology of soil testing and use of SHC to balance the dose of fertilizers for sustaining soil health. The half of the respondents found the technology beneficial for sustaining soil health, lowering the input cost and improving the farm production.
Keywords: Awareness; Adoption; Knowledge; Soil health cards and soil testing